Clinical Profile of Children Presenting with Intoxication on Emergency Departement Soetomo Hospital in 2011 - Ira Dharmawati; Neurinda Permata Kusumastuti; Arina Setyaningtyas (Universitas Airlangga, 2012)
Introduction: Acute poisoning in children is an important pediatric emergency and is a world wide problem, the majority of these poisoning incidents are unintentional and preventable. Based on data from WHO, the mortality of children under 4 years varies between 0.3–7% per 100,000 population in some countries in the world. The incidence, clinical proﬁle and the type of poison and the output of poisoning cases in children in Surabaya until now there is no deﬁnitive data. The objective of the study was to study the clinical proﬁle and outcome of childhood poisoning and intoxication in Soetomo hospital.Method: Design used in the study was a retrospective study done in children between 1 month and 18 years old of age who were admitted in emergency departement Soetomo hospital with diagnosis of acute poisoning between January until Desember 2012. Patients were proﬁled according to age, sex, poison consume and outcome.Result: There were 12 patients enrolled in the study. Male: female ratio was 2:1. The mean age of presentation was 53 months. Hydrocarbon poisoning was the commonest poisoning seen in (41.7%) patients followed by organophospat (33.3%) poisoning. During treatment, 58.3% received antibiotics, 25% patients who poisoning with organophosphat received antidots and 50% from all sample received antagonist histamin H2 because of stomached. Overall survival was 91,6%.Discussion: Hydrocarbon is the commonest agent involved in childhood poisoning. Overall, the outcome is good with 91,6% survival in our hospital.